2021
DOI: 10.3389/fpsyg.2021.701255
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Coping With Self-Regulated Distance Learning in Times of COVID-19: Evidence From a Longitudinal Study

Abstract: Due to the COVID-19 pandemic, students worldwide have experienced fundamental changes to their learning. Schools had to shift to distance education as part of the effort to stop the spread of the virus. Although distance learning undoubtedly resulted in challenges for all students, there is much concern that it exacerbated existing educational inequalities and led to disadvantages – particularly for students who were already struggling academically and lacking support from family and school. The aim of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 19 publications
4
36
1
2
Order By: Relevance
“…Some researchers even argued that whether students could succeed in the online learning largely depends on their online SRL ability (Serdyukov & Hill, 2013 ; Wang et al, 2013 ). Recently, the importance of SRL competence for online learning became particularly evident in the context of the COVID‐19 pandemic, and researchers have suggested that schools should strengthen their investment in promoting the development of students' SRL competencies (Berger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers even argued that whether students could succeed in the online learning largely depends on their online SRL ability (Serdyukov & Hill, 2013 ; Wang et al, 2013 ). Recently, the importance of SRL competence for online learning became particularly evident in the context of the COVID‐19 pandemic, and researchers have suggested that schools should strengthen their investment in promoting the development of students' SRL competencies (Berger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This points at distance education as having the potential to be part of students' learning in regular times. Other studies reported that, with support from parents and teachers, students could cope with distance learning [45], which means that it is possible to benefit from distance learning even in regular times.…”
Section: Algorithmic and Creative Processesmentioning
confidence: 99%
“…Verunsicherung, Einsamkeit, Lockdown und Distance Learning (Berger et al, 2021;Huber und Helm, 2020): Bereits vor der Pandemie litten mindestens 20 % der österreichischen Jugendlichen an psychischen Problemen (Wagner et al, 2017) So konnte mit dem Projekt open2chat durch Forschung schon vor der Pandemie der Bedarf eines niederschwelligen Behandlungsangebots als asynchron sowie synchron nutzbares Chat-Programm identifiziert und die Entwicklung bereits 2019 begonnen werden (Mägde et al, 2020). Bei der Entwicklung wurden Jugendlichen von Anfang an mit involviert (Mittmann, Schmalwieser, Diendorfer, Schrank, & Boeckle, 2022).…”
Section: Caring Als Gemeinsames Unterstützungsnetzwerkunclassified